License to grill / Chris Schlesinger, John Willoughby - Schlesinger, Chris
This is grilling designed for the novice or pro, the duffer or dedicated man, woman, or child. In addition to covering the basics, Chris and Doc add several new, lighter dimensions to their grilling canon, with more grilled vegetables, more seafood, more pasta, and more surprisingly grillable fruit. Vibrant and adventurous, the recipes combine fresh herbs, chiles, citrus, and spices with that indefinable grilled flavor to create dishes that both satisfy and intrigue. Special features of the book include an in-depth grill briefing, including tips on easy fire starting, answers to the ten most frequently asked grilling questions, five keys to easy grilling, and - for those who can't bear to put the grill away when the winter comes - a guide to fireplace grilling. Packed with practical grilling instructions, anecdotes, and inventive recipes that join simple pleasure with culinary adventure, here's a book that has direct appeal to anyone who's ever wanted to put food over fire. Whether you're a novice looking for your initial License to Grill, an accomplished live fire devotee ready to earn your Ph. G. (Doctorate of Grilling), or you just want to spend some time hanging out by the fire, this is the book for you.